Bibliometric analysis of evolutionary trends and hotspots of super-enhancers in cancer - Tang, Zhen-Chu; Qu, Qiang; Teng, Xin-Qi; Zhuang, Hai-Hui; Xu, Wei-Xin; Qu, Jian (Frontiers in Pharmacology, 2023)
Background: In the past decade, super-enhancer (SE) has become a research hotspot with increasing attention on cancer occurrence, development, and prognosis. To illustrate the hotspots of SE in cancer research and its evolutionary tendency, bibliometric analysis was carried out for this topic.Methods: Literature published before Dec. 31, 2022, in WOSCC, was systematically classified, and Citespace, Vosviewer, and GraphPad Prism analyzed the data.Results: After screening out inappropriate documents and duplicate data, 911 publications were selected for further bibliometric analysis. The top five research areas were Oncology (257, 28.211%), Cell Biology (210, 23.052%), Biochemistry Molecular Biology (209, 22.942%), Science Technology Other Topics (138, 15.148%), and Genetics Heredity (132, 14.490%). The United States of America (USA) has the highest number of documents (462, 50.71%), followed by China (303, 33.26%). Among the most productive institutions, four of which are from the USA and one from Singapore,